Integral Equation Analysis of Terahertz Backscattering from Circular Dielectric Rod with Partial Graphene Cover - Dukhopelnykov, Sergii V.; Sauleau, Ronan; Nosich, Alexander I. (IEEE journal of quantum electronics, 2020)
We study how the backward scattering crosssection (BSCS) of a microsize dielectric rod illuminated by an Hpolarized plane wave can be efficiently manipulated using a partial graphene cover and associated plasmon resonances. Our treatment is based on the hyper-singular boundary integral equation, discretized with a Nystrom-type algorithm, which has a mathematically grounded convergence. We compute the BSCS and the extinction cross-section (ECS) in the sub-THz and THz ranges with controlled accuracy and demonstrate that BSCS can be both enhanced and reduced due to the graphene strip.